Hydrogenation and silylation of a double-cyclometalated ruthenium complex: structures and dynamic behavior of hydrido and hydridosilicate ruthenium complexes - Scherl, Peter; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2013)
A double-cyclometalated ruthenium complex containing a chiral tripodal phospholane has been prepared by reaction with [Ru(η4-COD)(η3-methylallyl)2] via elimination of isobutene. The ruthenium-carbon bonds of this compound were reversibly cleaved by H2, resulting in an equilibrium between a tri- and a tetrahydride (4 and 5). T1 relaxation time measurements revealed the nonclassical nature of the fluctuating hydrides. Release of the gas led to complete re-formation of the cyclometalated compound. Reaction of 3 with D2 afforded D10-5, in which six ortho-phenyl protons and four hydrides were replaced by deuterium. Furthermore, diphenylsilane was found to readily insert into one Ru-C bond to form 6, containing a κ3-dihydridosilicate fragment. On the basis of deuterium labeling experiments, the fast exchange between the two hydrides was shown to include a reductive elimination/oxidative addition step involving the remaining metalated phenyl group. Again, pressurization of 6 with H2 resulted in reversible cleavage of the remaining Ru-C bond, yielding the corresponding trihydride 7.